2023
DOI: 10.3390/bioengineering10060650
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Rehabilitation Interventions for Motor Symptoms in COVID-19 Patients: A Narrative Review

Serena Cerfoglio,
Paolo Capodaglio,
Paolo Rossi
et al.

Abstract: The COVID-19 pandemic brought new challenges to global healthcare systems regarding the care of acute patients and the delivery of rehabilitation programs to post-acute or chronic patients. Patients who survive severe forms of COVID-19 often report incomplete healing and long-term symptoms. The need of these patients for rehabilitation has been recognized as a public health problem. In this context, the application of tele-rehabilitation has been explored to reduce the burden on healthcare systems. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Conventional rehabilitative approaches for PCC include physiotherapy [18,19], breathing [20] and resistance and/or aerobic exercises [21], psychological counseling [22], and home-based programs [23].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional rehabilitative approaches for PCC include physiotherapy [18,19], breathing [20] and resistance and/or aerobic exercises [21], psychological counseling [22], and home-based programs [23].…”
Section: Introductionmentioning
confidence: 99%
“…Tele-Neurorehabilitation (TNR) is an innovative approach that allows neurologically afflicted patients, who might not otherwise have access to healthcare facilities due to distance or economic issues, to continue cost effective rehabilitation at home ( Khanna et al, 2018 ). Numerous published studies ( Brennan et al, 2021 ; Cerfoglio et al, 2023 ; Cox et al, 2021 ; Iodice et al, 2021 ; Maresca et al, 2020 ; Matamala-Gomez et al, 2021 ; Srivastava et al, 2021 ) demonstrated the efficacy of providing remote, home-based telerehabilitation solutions to patients with neurological diseases during the COVID-19 pandemic.…”
mentioning
confidence: 99%